The network of the Regional Health Observatories in France (Italian Journal of Public Health, 2004)
The Regional Health Observatories (RHOs) were created in France in the 1980’s. They exist in each of the 26regions. Their principal mission is to assist in the decision making process by the undertaking of in-depthanalyses of the populations’ health status. To achieve this aim they catalogue and validate existing data,promote surveys when there is a lack of information, disseminate the collected information and conductevaluations of public health interventions.Around 400 people work in the observatories (241 full-time equivalents) with various expertise includingpublic health doctors, statisticians, sociologists, demographers, geographers, economists etc. More than40% of the budget of the RHOs comes from the government while 21% comes from the local executive.RHOs work with all the regional and local institutions concerned with health programs and policies. Themain role of the RHOs in this context is to identify the health needs, to describe health related behavioursand to describe the utilisation of the health care system. The analysis of the different kinds of workconducted shows the great diversity of the subjects treated by the observatories.The creation in 1989 of the “Fédération Nationale des Observatoires Régionaux de Santé” (FNORS)strengthened the links within the RHOs. Its role is to represent the RHO network and to facilitate theharmonisation of the inter-RHOs projects. Recently, the FNORS increase its position to represent RHOs at theEuropean level by taking part in EU projects and to promote the creation of a European network of regionalhealth observatories.
Keywords: Regional Health Observatories (RHO); Fédération Nationale des Observatoires Régionaux de Santé (FNORS)